Root and Shoot Growth of Eucalyptus Cuttings as Affected by the Position of the Rejuvenated Shoot on the Stock Plant - Babitha, M.; Sreenivasulu, A.; Meru, Elusing; Rao, P. S. (Indian Forester, 2000)
An experiment was conducted at Srinivasavanam Field Research Station, Tirupati, India to find out whether the position of the rejuvenated shoot on the Eucalyptus stock plant exerted any influence on the root and shoot growth of cuttings. The results revealed that the area of the largest leaf, percentage of sprouting buds, root length, fresh weight and moisture content of roots showed significantly higher values in respect of cuttings taken from coppice shoots of coppiced stump 7-13 cm above the ground. On the contrary, survival percentage, number of shoots, number ofleaves and number of roots per cutting did not differ significantly among the treatments. Hence it is ideal to harvest the juvenile coppice shoots from 7-13 cm height on the coppiced stump to produce good quality clones.